Arta actorului și re-prezentarea sinelui - Crișan, Sorin (Theatrical Research, 2025)
The Art of the Actor and the Re-Presentation of the Self The art of the actor is not a mere aesthetic manifestation of life, but, on the one hand, a way to explore the identity of the performer, and also, on the other hand, a means to build bridges between authenticity and dissimulation. Consequently, theatre reveals itself to us as a space of communion, heralding the presence of a certain agape, and as a locus centered on the relationship between self and other, by virtue of its particular way of negotiating the meaning of artistic expression and, equally so, in light of its being attuned to our innermost humanity. In this very same vein, theatre and love share a common destiny, namely that of becoming, or, as Heidegger would say, one of endless “possibility”. Just as the actor, through his art, transcends the boundaries of individuality, aspiring to become someone else, love also evokes the image of the other, contributing to the aim of imbuing meaning and significance into a message that oversteps the restrictive framework of subjectivity. If, for Sartre, relationships are to be marred by the angst implicit in the generic act of coming into contact with another (or more specifically, with the gaze and the judgment of others, the proverbial “inferno” alluded to by Garcin’s choice of words in No Exit), theatre offers us the opportunity to transcend this juncture, by way of the ʻOther’ being transmuted into a companion of our own becoming. Consequently, both theatre and love enable an authentic communion between ʻI’ and ʻYou’, through which the human being may fulfil its purpose on the stage of a perpetual rebirth. Simply put, the art of the actor does not merely entail a discipline of expression, but also an incomparable method through which one may be poised to inhabit the interstices between reality and fiction.